Effect of wastewater from cassava factories on water quality, growth and survival of Nile tilapia (Oreochromis niloticus) - Vo Van Vinh; Yakupitiyage, Amararatne; Preeda Pakpian; Gallardo, Wenresti G.; Berg, Hakan; Sida (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
The study was conducted in Tay Ninh from Ju ly to December 2007. Effects of cassava wastewater on aquatic environment were evaluated based on the questionnaires interviewed at Chau Thanh district and key respondents from Natural Resources and Environment Agencies. Test for cyanide (CN - ) concentration was carried out at 7 sites of Vinh river and 6 sites of Thanh Vinh factory. Ca ssava wastewater was collected at outlet of processing section (F0) for toxicity tests on tilapia fingerlings to find out Lethal Concentration 50 (LC50), Low Observed Effect Concentration (LOEC), and No Observed Effect Concentration (NOEC). The decompositi on of toxic cassava wa stewater was also determined by spatial and temporal conditions. Since 1997, the effluences of nearly 1,000 m 3 day -1 wastewater from three cassava factories have been identified by the key respondents. The pollution became seriously from 2004 with around 5,000 m 3 day -1 . Cassava wastewater ha d affected on the natu ral habitat of fish and caused the disappearance of the 27 comm on fish species during the operation of cassava factories, of which 6 fish species ha ve not been seen sinc e the cassava factories established. Most of the cage culture farm ers (93%) were failed their crop by cassava wastewater. In Vinh River, the concentrations of CN - were annually fluctu ated by velocity, the lowest (6.1 og L -1 ) in August rainy season and the highest 64.2ogL -1 recorded in October dry season. On the othe r hand, concentrations of CN - was decreased by time in the waste-pond system in Thanh Vinh factory, the highest 17,609.61og L -1 at F0 and lowest 70.44ogL -1 at F4. The LC50 of cassava waste was determined at 0.315% (i.e. 55.47og.L -1 ) by using Probit software. At th e concentration of 0.05% (8.8og.L -1 ) cassava wastewater, the fish weight gain had no si gnificant difference from the cont rol (NOEC). In contrast, the concentration of 0.10% wastewater affected to tilapia growth rate (LOEC). Additionally, toxic decomposition was performed by mortality of fish. There was no effect observed on fish by 1% concentration of wastewater after 6 hours under aeration condition and 18 hrs with no aeration. The cassava wastewater were collected at 6 sites of Thanh Vinh factory showed that toxic levels were decreased al ong with waste treatment pond system. All fish were died by 1% of wastewater collected at F0 and F0c and no death fish was observed when they were exposed to the wastewater from the second (F2) backward. The study contributes the valuable information and da ta for strategic management of cassava wastewater and natural resource in the region.
A thesis submitted in partial fulfi llment of the requirements for the degree of Master of Science in Aquaculture Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Nile tilapia -- Effect of water quality on; Cassava industry -- Vietnam